Optimisation of lipid-lowering therapy post-Acute Coronary Syndromes: a multidisciplinary, cross-interface novel pharmacy care model within a local cardiac rehabilitation centre - Idil Z. Gul; Sarah Baig; Maria Glover; Mandeep Virdee; Samira Osman; Duncan Jenkins; Zahraa Jalal (Journal of Pharmaceutical Policy and Practice, 2025)
Background Acute coronary syndromes (ACS) are a spectrum of diseases that diminish blood flow to the heart and are a major cause of global death. They can be prevented with lipid-lowering therapies (LLTs) but these are often sub-optimally managed in practice. A potential solution could include implementing independent prescribing (IP) pharmacists to optimise LLTs within cardiac rehabilitation services. Aim: To explore the impact of a novel pharmacy service within a cardiac rehabilitation centre (CRC) at a local hospital in the West Midlands UK, on post-ACS patients’ ability to achieve targets of non-HDL-C.Methods A retrospective analysis was undertaken at a rehabilitation centre to evaluate pharmacist interventions in lipid management. Inclusion criteria: Post-ACS patients not attaining target levels of non-HDL-C < 2.5 mmol/L, 3 months after discharge. Non-HDL-C levels were also measured 2 months after the pharmacist interventions.Results 169 post-ACS patients were eligible for treatment. 54% of patients achieved their <2.5 mmol/L of non-HDL-C levels. 25% of these were combination therapy of high-intensity statin and ezetimibe. 36% of patients achieved a 40% reduction of baseline non-HDL levels. 38% did not achieve either target.Conclusion This innovative pharmacy role in CR could address the suboptimal LLT management that is common in the post-ACS population. It fosters collaborative care across healthcare sectors, improving patient outcomes and augmenting the probability of reducing ACS risk.